Analisis Penyajian Laporan Keuangan Koperasi Syariah (Studi Kasus Pada BMT Muda Dan KJKS BMT Amanah Ummah Di Surabaya) - Nabilah Nabilah; Noven Suprayogi (Universitas Airlangga, 2016)
Sharia cooperative is subject to use the PSA Sharia guideline 100 and 101 on the process of arranging and presenting financial report. The fact is that there are a lot of financial report presentation that is less suitable with the PSAK Sharia. This research aims at determining the reasons why do the financial report presentation is less suitable with the PSAK Sharia 100 and 101.This research utilizes qualitative approach with exploratory case study method. Data collection is done by interviewing informant with resource triangulation validation method.The result of this research shows that sharia cooperation tends to use Indonesian Accounting Standards Non-Publicly-Accountable Entities (SAK ETAP) when presenting the financial report since there is a Ministrial regulation of Cooperatives and Small-Medium Enterprises number 4 in 2012 that obliged all the cooperatives in Indonesia to use SAK ETAP guide.